UTILIZING SONG âTHERE IS AN ANIMALâTO TEACH VOCABULARY AND BASIC SENTENCE STRUCTURE TOYOUNG LEARNERS THROUGH THREE STAGES ACTIVITY - Priyo Atmojo, Arief Eko (978-602-7561-566)
Â  Â  Â  Â  Â  Â Â This paper aims to describe the importance, role, and implementation of using song âThere is an Animalâ to teach vocabulary and basic sentence structure to young learners through three stages activity.Some experts argue that children will have higher chances to become more proficient if they begin learning a second language earlier rather than learning it later.Children can learn as many spoken language as we allow them to hear systematically and regularly at the same time. In childrenâs class,a positive learning atmosphere can be created by providing favourable environment, useful resources, carefully structured input, and practice opportunities. An effort which can be done is by utilizing song. The use of song in teaching English to young learners gives lots of benefits and advantages. The development of songs into language learning tasks can be a way to optimize advantages and minimize limitations of the use of songs.To utilize song as a powerful tool to teach English for children, there are many strategies which can be used. These strategies are about transforming singing song as an activity into a well-planned and structured classroom task by utilizing the song. Classroom tasks for young learners have three stages that once can beidentified,analyzed, adapted, and expanded.Therefore, songs must be developed into a task with preparation, core, and follow-up stages which in result can help transferring the words in the song into use and maximize the potential of songs as teaching and learning tools.Â Keywords: children, song, teaching English as foreign language (TEFL), young learners.